Supporting Optimal Infant, Young Child and Maternal Nutrition and Health in Jordan: FY2021 1st Quarter Report October 1st - December 31st, 2020. - Feed the Future Jordan Nutrition Innovation Lab. (Tufts University. Tisch Library., 2023)
The following is the quarterly report of the Feed the Future Jordan Nutrition Innovation Lab for the fiscal year 2021, starting from October 1st, 2020 until December 31st, 2020.; Keywords: nutrition, maternal and infant young child nutrition, human and institutional capacity, stakeholder engagement.; Leader with Associate Cooperative Agreement No. AID-OAA-LA-10-00006 Under Feed the Future Innovation Lab for Nutrition, Tufts University, Friedman School of Nutrition Science and Policy Cooperative Agreement Associate Award No.: 72027820LA00003.